Use of Unity in Scientific Simulation and Modeling for Research and Education - Hutchins, Nathan (2020)
Simulation and Modeling in scientific research and education is very important when it comes to displaying results to the scientific community as well as the public. This can be very time consuming using the standard scientific tools with very minimal results. The University of Tulsa’s Vehicle Intelligence and Autonomy Lab (VAIL) has begun using the C# based game engine Unity for the development of simulations in research and classroom settings. This paper compares the use of MATLAB and Unity for the simulation, modeling, and informational display portion of an ideal Newton’s Cradle project. Using the ideal Newton’s Cradle as the example allows us to verify and validate the accuracy and usefulness of Unity as the modeling and simulation of systems under development by VAIL. Unity has been verified in two ways, first, MATLAB was used to develop the behavioral model of the ideal Newton’s Cradle then the output was imported into Unity for verification and validation. Second, the ideal Newton’s Cradle model was developed entirely in Unity, using C#, and then the result was compared to MATLAB, again, for verification and validation. The results of VAIL testing on Unity are very positive. Using Unity, VAIL is able to more quickly develop Simulations and prototypes for the current research.